Demanding clients state their case: Comments on the client round table at La Rochelle (SFT universite d'ete, July 2002) - Chris Durban (JoSTrans: The Journal of Specialised Translation)
Linguists are as vulnerable as the most hapless monolingual buyer of translation when a debate takes place in a language they do not speak or read. The author draws reader's attention to a discussion of translation quality and priorities by three demanding buyers of financial translation, and highlights issues that might be of interest to students, teachers and practicing translators. The text of the round table can be accessed in French at http://www.sft.fr/dossiers/actesrochelle/8acheteurs.pdf